Eager to leave? Populist radical right parties' responses to the UK's Brexit vote. (February 2020) - van Kessel, Stijn; Chelotti, Nicola; Drake, Helen; Roch, Juan; Rodi, Patricia
Populist radical right parties are naturally Eurosceptic. Many responded positively to the British referendum vote to leave the European Union; various observers even spoke of a potential populist radical right-instigated 'domino effect'. We ask whether this Brexit-enthusiasm prevailed in the proximate aftermath of the UK referendum, by means of a comparative analysis of populist radical right parties' national election campaigns in the Netherlands, France, Germany, and Italy. The analysis considers whether the UK referendum result served as an external stimulus for populist radical right parties to harden their Euroscepticism and politicise the issue of European integration. The results show that this has, generally speaking, not been the case, and that Brexit has also not stimulated or amplified calls for leaving the European Union. Relating our findings to literature on the politicisation of European integration and strategic party behaviour, we argue that populist radical right parties had few incentives to act differently given the uninviting political opportunity structure.